Media dan Gender - Safitri, Evis Diah (Mekomda: Media Komunikasi Dakwah, 2024)
The presence of various private television stations in Indonesia has facilitated the dissemination of information to the public. Private stations with their economic logic place the audience and advertisers as their market, so that the program which is their marketing product is presented with the most attractive packaging according to the wishes of the market If observed, most of the products on the market have been advertised through television. There are even some advertising agencies that make television a powerful medium to compete against competitors in offering products. Even though placing advertisements on broadcasting stations is calculated to have the most expensive rates compared to other communication media rentals. Advertising as a mass communication system becomes a parameter or implementation of gender discourse that challenges the biases of gender inequalities. Advertising now tends to be a means of legitimizing ideological hegemony and preserving the dominance of patriarchal ideology. The tendency to use advertising as an example of a form of subordination of women is easily raised because the gender bias of advertising will affect the way we think about the role and functioning of gender in society.